Effects of a whole body vibration training program on strength, power, and functional tests in the physically active elderly - Renata Gonçalves da Silva; Rosana Andreotti; Paula Regina Gehring; Marcelo Eduardo de Souza Nunes; Lilian Wallerstein; Maria Cecília Oliveira da Fonseca; Sueli Santos; Valmor Tricoli; Carlos Ugrinowitsch (Universidade Federal de Santa Catarina, 2009)
The aim of this study was to investigate the effect of a whole body vibration training program on knee extensor isokinetic peak torque, average power, and functional tests in the physically active elderly. Forty-seven subjects, who participated in a training program for the elderly, were recruited. The subjects were divided into two groups: whole body vibration group (WBV) (n=24, 70.7±5.8 years, 62.7±12.3 kg and 155.9±8.0 cm ) and control group (n=23. 70.0±5.7 years, 65.3±10.7 kg and 157.9±6.6 cm). The WBS group underwent whole body vibration exercise and their regular training program for 13 weeks, 2 times per week, whereas the control group performed the regular training program only. Whole body vibration training was not effective in increasing isokinetic peak torque, average power, or performance in the functional tests. On the other hand, the regular training program was effective in increasing elbow flexor strength endurance, distance covered in the 6-min walk test, and speed in the timed up and go test. The results suggest that vibration training is not effective in modifying functionality or muscle strength and power in the physically active elderly.